Evidence for the involvement of lipid rafts localized at the ER-mitochondria associated membranes in autophagosome formation. Issue 6 (2nd June 2016) - Garofalo, Tina; Matarrese, Paola; Manganelli, Valeria; Marconi, Matteo; Tinari, Antonella; Gambardella, Lucrezia; Faggioni, Alberto; Misasi, Roberta; Sorice, Maurizio; Malorni, Walter
ABSTRACT: Mitochondria-associated membranes (MAMs) are subdomains of the endoplasmic reticulum (ER) that interact with mitochondria. This membrane scrambling between ER and mitochondria appears to play a critical role in the earliest steps of autophagy. Recently, lipid microdomains, i.e. lipid rafts, have been identified as further actors of the autophagic process. In the present work, a series of biochemical and molecular analyses has been carried out in human fibroblasts with the specific aim of characterizing lipid rafts in MAMs and to decipher their possible implication in the autophagosome formation. In fact, the presence of lipid microdomains in MAMs has been detected and, in these structures, a molecular interaction of the ganglioside GD3, a paradigmatic "brick" of lipid rafts, with core-initiator proteins of autophagy, such as AMBRA1 and WIPI1, was revealed. This association seems thus to take place in the early phases of autophagic process in which MAMs have been hypothesized to play a key role. The functional activity of GD3 was suggested by the experiments carried out by knocking down ST8SIA1 gene expression, i.e., the synthase that leads to the ganglioside formation. This experimental condition results in fact in the impairment of the ER-mitochondria crosstalk and the subsequent hindering of autophagosome nucleation. We thus hypothesize that MAM raft-like microdomains could be pivotal in the initial organelle scrambling activity that finally leads to the formation of autophagosome.